Multidisciplinary valuation of the diabetic foot - Isabel Sánchez Reyes; Rafael Jorge Pérez Pérez; Jose Manuel Hernández Romero; Mª Jesús Martín González; Alfredo Castro Díaz; Rocío López Cueto (Fundación para el Desarrollo de la Enfermería, 2010)
Conventional classifications for diabetic foot, among them, Wagner Classification, do not contemplate the criteria or sichemia, neuropathy and infection, pillars that sustain the etiopathogy of this syndrome. With Modified Wagner Classification (MWC), there are cleary defined the phase and characteristics of the wound, incorporatin into the anatomical description by a graphical way (letters in capital letter or small one) the mentioned props (infection, neuropathy and ischemia). In this way not only the language is equal (comes to an agreement) to avoid interpretation mistakes, but also it is orientated by just one number and a letter towards a prognosis and treatment criteria. Cases received before and after the use of the MWC are compared perfoming a review, by two different professional groups, being catalogued by the same numbers in a high percentage. That is why we recommend its diffusion and generalized the employment for the managing of the diabetic foot.